Kemampuan Pemahaman Konsep Matematis Siswa pada Materi SPLDV Menggunakan Soal-soal Berbasis Taksonomi SOLO - Fathonah, Dede; Hapsari, Trusti; Firmasari, Siska (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2021)
Story questions have level of abstraction characteristics. In the story question, it can be seen that the student' abstract extended level by changing the pattern questions according to the indicators of high-level mathematical thinking. This study aims to determine the ability of students to understand mathematical concepts in the SPLDV material using SOLO Taxonomy-based questions and student responses in working on these questions. When researchers did a teaching practice at a vocational high school in Cirebon district, they found that the students' ability to understand concepts was still low, this was confirmed by interviews with students that they did not understand SPLDV questions, especially in making mathematical models of a story problem. This research is located in one of the Vocational High Schools in Cirebon Regency. The subjects of this study were 21 class X students. The researcher used a descriptive method with a qualitative approach because the researcher wanted to find out more about how students understood mathematical concepts in the SPLDV material using SOLO Taxonomy-based questions. The results of this study were the students' ability to understand mathematical concepts in the SPLDV Material Using SOLO Taxonomy-based questions was still very low, namely 37.10% and the responses given by students were positive for the use of questions based on the use of SOLO Taxonomy-based questions.